Improving Skills in Creating Promotional Content at Agro Eduwisata Organik (AEWO) Mulyaharja Village Bogor City - Jayawinangun, Roni; Valdiani, Dini; Ono, Dipo Krishyudi; Afriansyah, Ari; Permatasari, Olivia Devita; Anggraeni, Khori Aulia Ria (Research Collaboration Community (Rescollacom), 2024)
Agro Eduwisata Organik (AEWO) Mulyaharja is one of the natural and educational tourism in Bogor City and is one of the leading ecotourism in Bogor City which is managed by the Tourism Movement Group (Kompepar). As one of the leading destinations, AEWO Mulyaharja still has many challenges, namely limited skills and promotional media. This community service activity consists of five stages, namely situation analysis, socialization, training, mentoring and evaluation. The training method uses lectures and practices with materials related to social media, social media features, design, video content and video editing. The results of this activity are increased knowledge and skills of Kompepar AEWO Mulyaharja partners regarding the creation of promotional content in the form of images and videos on social media, the use and steps using the Canva and Capcut applications, increasing the number of followers, posts and Engagement rate (ER) on Instagram, adding official accounts on other social media, namely YouTube, X and TikTok